EMPLOYERS PERCEPTION OF COMPUTER-BASED COMPETENCIES REQUIRED OF TECHNICAL COLLEGE GRADUATES FOR EMPLOYMENT IN RIVERS STATE (NAU Journal of Technology and Vocational Education, 2024)
The study ascertained the perception of employers on the computer-basedcompetencies required of technical college graduates for employment in Rivers State.Four research questions guided the study and four hypotheses were tested at 0.05level of significance. A descriptive survey research design was adopted for the study.The population for the study comprised all 440 employers of technical collegegraduates in public and private establishments in 23 Local Government Areas ofRivers State. Proportionate stratified random sampling technique was used indrawing137employers (public: 42, private: 95) in 14 Local Government Areas. Theinstrument for data collection was a four point rating scale structured questionnairedeveloped by the researcher and validated by experts. Through the use of CronbachAlpha method, the instrument was found to an overall reliability coefficient of 0.81.Mean and standard deviation were used to answer the research questions anddetermine the closeness of the respondents’ view. While the hypotheses were testedusing z-test. The study showed that employers were of the view that word-processing,spreadsheet, computer aided design and networking competencies are required oftechnical college graduates for employment. The study revealed that there was nosignificant difference in the mean perception of employers on word-processing,computer Aided design and networking competencies required from technical collegegraduates for employment; while there was significant difference in the meanperception of employers on spread sheet competency required from technical collegegraduates for employment. The study recommended among others, that Stategovernments and College heads should provide and maintain adequate computerfacilities in technical colleges to equip the students with relevant competencies forwork performance.
Keywords: Technical and Vocational Education, Computer-Based Competencies, Perception, Employment.